Measurement of ultra-low ion energy of decelerated ion beam using a deflecting electric field - P. Thopan (2018)
© 2015 Elsevier B.V. In investigation on ultra-low-energy ion bombardment effect on DNA, an ion beam deceleration lens was developed for high-quality ultra-low-energy ion beam. Measurement of the ion energy after deceleration was necessary to confirm the ion beam really decelerated as theoretically predicted. In contrast to conventional methods, this work used a simple deflecting electrostatic field after the deceleration lens to bend the ion beam. The beam bending distance depended on the ion energy and was described and simulated. A system for the measurement of the ion beam energy was constructed. It consisted of a pair of parallel electrode plates to generate the deflecting electrical field, a copper rod measurement piece to detect ion beam current, a vernier caliper to mark the beam position, a stepping motor to translate the measurement rod, and a webcam-camera to read the beam bending distance. The entire system was installed after the ion-beam deceleration lens inside the large chamber of the bioengineering vertical ion beam line. Moving the measurement rod across the decelerated ion beam enabled to obtain beam profiles, from which the beam bending distance could be known and the ion beam energy could be calculated. The measurement results were in good agreement with theoretical and simulated results.